Zaznavanje uporabnosti in vrednosti znanja za poklic med dijaki in študenti - Mlinarič, Vesna (Šolsko polje, 2013)
The social perception of the applicability of knowledge in the occupation, and its value in society has been studied among the young generation in Slovenia. The aim of the study was to find out if the social changes in the priorities of the value of knowledge are reflected in the social representation of knowledge in relation to the individual occupational choices, perceived employement criteria, and the reputation of vocations in the society. The study was conducted on the representative samples of students in high-school (N = 470), and in university (N = 832) in the school year 2011/12. The students from three types of high-school participated: vocational, special-technical schools and gymnasium. The students of various study programs from three public universities also participated: University of Ljubljana, University of Maribor, University of Primorska. The results show that the perception of knowledge in occupation is related to the developmental differences and the type of educational program. The perception of the social value of the educational courses and the reputation of vocations is similar in both samples. The latter is assumed as the reference for the students in defining their own occupational status.
Keywords: knowledge; znanje; družba znanja; occupational choices; stališča; attitudes; value of knowledge; vrednost znanja; youth; poklicne izbire; mladi; students; študenti; student; social perceptions; socialne zaznave; education; vzgoja in izobraževanje